Soldiers of the French Revolution - Forrest, Alan (Bicentennial Reflections on the French Revolution, 1989)
In this work Alan Forrest brings together some of the recent research on the Revolutionary army that has been undertaken on both sides of the Atlantic by younger historians, many of whom look to the influential work of Braudel for a model. Forrest places the armies of the Revolution in a broader social and political context by presenting the effects of war and militarization on French society and government in the Revolutionary period.Revolutionary idealists thought of the French soldier as a willing volunteer sacrificing himself for the principles of the Revolution; Forrest examines the convergence of these ideals with the ordinary, and often dreadful, experience of protracted warfare that the soldier endured